Bioaccessibility and intestinal uptake of carotenoids from microalgae Scenedesmus obliquus. (April 2021) - do Nascimento, Tatiele C.; Pinheiro, Pricila N.; Fernandes, Andressa S.; Murador, Daniella C.; Neves, Bruna V.; de Menezes, Cristiano R.; de Rosso, Veridiana V.; Jacob-Lopes, Eduardo; Zepka, Leila Q.
Abstract: This study aimed to investigate the carotenoids bioaccessibility of the whole dried biomass (WDB), wet ultrasonicated biomass (WUB), and isolated carotenoid extract (ICE) from Scenedesmus obliquus using an in vitro digestion model. Also, the intestinal uptake of ICE was investigated. The samples were submitted to in vitro digestion model according to the INFOGEST protocol, and Caco-2 cells determined the intestinal uptake. Carotenoids were determined by HPLC-PDA-MS/MS. The results showed that the bioaccessibility was improved according to the type of product (ICE > WUB > WDB). The all- trans -canthaxanthin (99.07%), all- trans -α-carotene (48.94%), and all- trans -β-cryptoxanthin (31.87%) were the most bioaccessible compounds in ICE, WUB, and WDB, respectively. Due to the ICE showed the best bioaccessibility, it was considered the most efficient condition and subjected to uptake by intestinal cells. ICE uptake demonstrated that the most abundant carotenoids in Caco-2 cells were all- trans -β-crocoxanthin (17.34%), followed by all- trans -echinenone (7.55%). In contrast, all- trans -lutein (0.88%) was the least abundant in cells. The xanthophylls were uptake in greater proportion than carotenes. Finally, the results showed the significant influence of the product nature in promoting the bioaccessibility of microalgae carotenes and xanthophylls. Highlights: Bioaccessibility of S. obliquus carotenoids was determined for the first time. Different use forms determine the bioaccessibility of S. obliquus carotenoids. Carotenoids of the isolated extract are more bioaccessible than biomass. Xanthophyll are more bioaccessible and uptake in greater proportion than carotenes. The all- trans -β-crocoxanthin is the most abundant in Caco-2 cells.